2012
DOI: 10.1073/pnas.1114661109
|View full text |Cite
|
Sign up to set email alerts
|

Intramembrane proteolysis ofToxoplasmaapical membrane antigen 1 facilitates host-cell invasion but is dispensable for replication

Abstract: Apical membrane antigen 1 (AMA1) is a conserved transmembrane adhesin of apicomplexan parasites that plays an important role in host-cell invasion. Toxoplasma gondii AMA1 (TgAMA1) is secreted onto the parasite surface and subsequently released by proteolytic cleavage within its transmembrane domain. To elucidate the function of TgAMA1 intramembrane proteolysis, we used a heterologous cleavage assay to characterize the determinants within the TgAMA1 transmembrane domain (ALIAGLAVGGVLLLALLGGG-CYFA) that govern i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 33 publications
3
48
0
Order By: Relevance
“…Another sidechain preference has been found at P4 (Strisovsky et al, 2009), where some, but not all (Moin and Urban, 2012; Parussini et al, 2012), rhomboid enzymes prefer large hydrophobic residues. The substrate P4 valine formed hydrophobic interactions with F146 and M120 on the L1 loop (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another sidechain preference has been found at P4 (Strisovsky et al, 2009), where some, but not all (Moin and Urban, 2012; Parussini et al, 2012), rhomboid enzymes prefer large hydrophobic residues. The substrate P4 valine formed hydrophobic interactions with F146 and M120 on the L1 loop (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
“…Some rhomboid enzymes (Strisovsky et al, 2009), but not others (Moin and Urban, 2012; Parussini et al, 2012), also display a preference for hydrophobic P4 residues for efficient substrate proteolysis. With GlpG, the P4 sidechain forms a shallow but specific interaction with the top of the L1 loop.…”
Section: Discussionmentioning
confidence: 99%
“…30 years ago, found in T. gondii more recently, conserved in all apicomplexa, and shown recently to be an important component of the moving junction during invasion [50] and to contribute to intracellular tachyzoite multiplication [40] although this latter point is disputed [39]. Reducing AMA1 expression clearly impacts invasion and is therefore likely to affect virulence, but whether the gene is truly essential or not is not known [51].…”
Section: Transient Surface Proteins: Micsmentioning
confidence: 97%
“…One of them, named ROM4 acts on the microneme protein AMA1 [38] and has been shown to be crucial to invasion, as interfering with this cleavage inhibits invasion [39], and also to control indirectly the intracellular proliferation of tachyzoites as the impairment of AMA1 cleavage after the completion of invasion was shown to have a major impact on the triggering of development [40].…”
Section: Resident Surface Proteins and Lipidsmentioning
confidence: 99%
“…Mutations of the TgAMA1 tail lead to abortive invasion characterised by an intact MJ but non-penetrative tachyzoite (Sheiner et al, 2010;Lamarque et al, 2014). It is also possible that the tail, which remains in the invaded zoite after shedding of the ectodomain (Howell et al, 2003(Howell et al, , 2005Buguliskis et al, 2010;Olivieri et al, 2011), plays a role in coordinating the intracellular replication cycle, although this is yet to be resolved (Santos et al, 2011;Parussini et al, 2012). It has already been shown that phospho-signalling on the P. falciparum AMA1 tail plays an important role in the invasion process, specifically phosphorylation of Ser610 by protein kinase A (Treeck et al, 2009;Leykauf et al, 2010).…”
Section: The Ama1 Cytoplasmic Domain As a Signalling Componentmentioning
confidence: 97%